Effect of vitamin D supplementation, directly or via breast milk for term infants, on serum 25 hydroxyvitamin D and related biochemistry, and propensity to infection: a randomised placebo-controlled trial. Issue 1 (17th May 2016) - Chandy, David D.; Kare, Jahnavi; Singh, Shakal N.; Agarwal, Anjoo; Das, Vinita; Singh, Urmila; Ramesh, V.; Bhatia, Vijayalakshmi
Abstract: We assessed the effect of vitamin D supplementation on related biochemistry, infection and dentition of the infant. In a double-blind, placebo-controlled trial conducted in Lucknow, India (latitude 26°N), 230 mother –newborn pairs were randomised to receive, for 9 months, 3000µg/month oral vitamin D3 by the mother (group A) or 10µg/d by the infant (group B) or double placebo (group C). All babies received 15 min of sun exposure (unclothed) during massage. Infants' median 25-hydroxyvitamin D (25(OH)D) was lower in group C (median 45·3; interquartile range (IQR) 22–59·5 nmol/l) than in groups A (median 60·8; IQR 41·3–80·5 nmol/l ( P <0·01)) and B (median 61·3; IQR 41·3–75·3 nmol/l ( P <0·05)) at 3·5 months. Infant 25(OH)D correlated negatively with infant parathyroid hormone ( r −0·46, P <0·01). Elevated alkaline phosphatase (>7.5µkat/l) was significantly more frequent in group C babies (16 %) than in group A (4 %) or group B (0 %) babies. The number of days with respiratory or diarrhoeal infection by 9 months of age was higher in group C (median 46·5; IQR 14·8–73·3 d) than in group A (median 18·5; IQR 8·8–31·0 d ( P <0·01)) or group B (median 13·0; IQR 7·0–28·5 ( P <0·05)). We conclude that monthly maternal or daily infant supplementation with vitamin D along with sun exposure is superior to sun exposure alone in maintaining normal infant 25(OH)D at 3·5 months, and provide protection from elevated alkaline phosphatase and infectious morbidity.